Comprehensive evaluation of the aggressive certain degree of the chemical components in water to concrete - Doan, Thy Truc (Frontiers in Built Environment, 2024)
Evaluation and research on the aggressive degree to concrete were done in the previous research. However, the evaluation of aggressive certain degree in water to the concrete was experimented comprehensively in the laboratory by the Viet Nam Standard “TCVN 3994:1985” and ISO 14911:1998. In addition, this paper considers water with the chemical name “Chlorite-Bicarbonate-Sodium-Magnesium” by the Kurlov formula and “TCVN 81:1981”. Especially, comprehensive consideration of chemical analysis that includes Cation (Ca2+; Mg2+; ∑(Fe2+; Fe3+; Na+; K+; and NH4+); Anion (Cl−; SO42−; HCO3−; CO32− and OH−); and the other special items analysis which includes Permanent and Temporary hardness; Alkalinity; CO2 free; CO2 corrosive; Total mineralization; pH value; Nitrite (NO2−); and Nitrate (NO3−). The research results presented “water with chemical characteristics can’t create the aggression in concrete,“ which shows pH concentration is 5 and CO2 corrosion is 20 mg/l (approximately 0.04%); whereas ion Mg2+ is 1.5 g/l (approximately 3%) and SO42− is 0,25 g/l (approximately 0.5%). The total salt content in the presence of an evaporating surface obtains 12,5 g/l (approximately 25%). So research results can be used safely for the design or construction of the reinforcement concrete structures in My Thai Canal Bridge, Rach Gia town, Kien Giang province, Viet Nam, and Construction or Geotechnical as good reference documents in the future.